A chemical and mineralogical study of a soil profile near George - Lambrechts, J. J. N.(Johannes Jacobus Nicolaas) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric) -- University of Stellenbosch, 1964.